CHARACTERISTIC OF MUS-01 WING’S STRUCTURE TESTING MODEL - Aryandi Marta; Atik Bintoro; Riki Ardiansyah (National Institute of Aeronautics and Space - LAPAN, 2018)
The characteristic model of MUS-01 wing structure testing has been performed. Planned, this model will be used as an unmanned wing of the LSU-03NG. The test model is made of composite type e-glass. At the time of testing the structure test model is loaded according to MTOW weight. This research method also involves the unmanned aircraft mission, especially on the model test structure, model dimension, and direct experiment in the form of loading on the test model. The result of characterization of the test model during test, showed that the indicated test model has the characteristics as a test model that is unable to accept the unmanned operational load of LSU-03NG series aircraft. So it can not be used as a consideration for the structure of the unmanned aircraft.